الإحالة الموصولية ودورها في تحقيق الترابط النصي في شعر "سليمان العيسى" ديوان الجزائر نموذجا - زمـاش, مصطفى (حوليات المخبر, 2016)
يسعى هذا المقال إلى تتبع الإحالة بالأسماء الموصولة في ديوان الجزائر لسليمان العيسى إذ تميّز بحسن اختيار الإحالة المناسبة للمكان الأمثل بحسب ما يقتضيه مقام الكلام والأغراض الشعرية المرعية بما أضفى على مقطوعاته مسحة جمالية ووصل بين أطراف كلماتها المنساقة في انسياب مسبوكة محبوكة فخرجت مخرجا واحدا وربط كل ذلك بالمرمى الأسمى وهو نصرة ثروة الجزائر العظمى.  This article seeks to trac the process of subordination through the use of relative pronouns in Suleiman ElAissa's poems entitled "Diwan ElJazair". i.e collection of poems dedicated to Algeria. ElAissa's poems art characterized by the appropriate and skillful use of subordination. which meete the poet's thematic and stylistic aims. thus endowing his poems with an aesthetic touch. This stylistic device. moreover. creates a harmonious equivalence and correspondence between vocabulary. which in turn reinforces the cohesive and coherent texture of the poems. In doing so. the poet consolidates the overall theme. i.e. the glorificatio of the Algerian Revolution.